Taller sobre Conservación de Semillas para la Restauración Ecológica - Ulian, T.; Rovere, A.; Muñoz, B. (Ecosistemas, 2008)
Ulian, T. Rovere, A. Muñoz, B. (2008). Taller sobre Conservación de Semillas para la Restauración Ecológica. Ecosistemas17(3): 147-148.